The phenomenon of absence of members of the Parliament in Iraq and its impact on controlling sessions - PhD. Assistant Teacher Iman Qasim Hani Al-Safi (The college of law and political science journal, 2024)
The phenomenon of absence of members of the Parliament in IraqAnd its impact on controlling sessions      The member of the Representative Council constitutes the main key to moving the legislative authority, through the main roles assigned to him, whether at the national level as a representative of the nation, or through his local role as the product of his constituency that brought him to the parliamentary seat, and all of this is for the sake of parliamentary performance that pushes the legislative institution to  The imam is to embody its independence, and at the same time constitutes a recognition of the value of the members at the legal level.      However, on the realistic level, the phenomenon of absence is observed, which has cast a shadow over the legislative institution. The seats of the Representative Council have become vacant during discussions and during voting. This is all due to the control of the executive authority, in addition to the absence of deterrent legal texts that force members of the Representative Council to attend.     Hence the importance of the research we are dealing with, in the necessity of the representative’s commitment to the tasks entrusted to him, of which the duty of attendance is one of the most prominent, important and valuable, as this duty is the foundation from which all other parliamentary duties emerge.